AKSES KETERBUKAAN INFORMASI PUBLIK TERHADAP PENGGUNAAN DANA DESA: Studi di Desa Wawotimu Tomia Timur Kabupaten Wakatobi - La Ode Muhaimin; Nasrin Nasrin; Sitti Aisyah; Ririn Ririn (Jurnal Ilmu Hukum Kanturuna Wolio, 2022)
In accordance with the problems studied, the research conducted is a qualitative research which aims to determine the access to public information disclosure on the use of Wawotimu Village funds and the inhibiting factors for accessing public information openness to the use of Wawotimu Village funds. This study took 5 (five) respondents consisting of the Village Government and the Wawotimu Village community. Methods of data collection using in-depth interview techniques, documentation, and literature study. The results of this study indicate that access to public information disclosure on the use of Wawotimu Village funds has not been maximally managed properly by the Village Government, in terms of providing information on the use of Village funds, the Village Government only presents information in the form of APBDesa information which is displayed using a baleho on the Village information board. Meanwhile, the statement of the accountability report which is the most important thing for the public to know is not carried out as stated in the Minister of Home Affairs Regulation Number 20 of 2018 concerning Village financial management.